Motion mapping of the heterogeneous master–slave system for intuitive telemanipulation. (10th January 2018) - Gong, Daoxiong; Zhao, Jin; Yu, Jianjun; Zuo, Guoyu
Heterogeneous master–slave robots are widely used as both the assistive robot system for the elder/disabled people and the teleoperation robot system in dangerous environments. For the sake of intuitive teleoperation, motion mapping should be applied to keep the slave arm possessing the similar configuration of the master arm in the whole course of telemanipulation. We propose a motion mapping on the joint analog level based on unit dual quaternions (UDQs) for the telecontrol of a heterogeneous slave robot arm via the motion of human master arm. First, we analogize the links of the slave robot to the links of the human master arm, and accordingly group the slave arm joints into "shoulder, " "elbow, " and "wrist" joint analog sets. Then, we capture the motion of the human master arm via a wearable motion capture system and take it as the motion order of the slave arm. Finally, we solve the motion of slave robot arm's joint via UDQ-based 1-, 2-, and 3-Degree of freedom (DOF) orientation error UDQ decomposition algorithms that are suit for solving a typical class of robotic slave arms. As a result, the operator can manipulate the heterogeneous robot system intuitively and conveniently, and the fatigue degree and error rate of the user can be significantly reduced, and thus the safety of teleoperation in an unstructured and constrained environment can be significantly improved.